Re-Evaluating Natural Resistance to Herpes Simplex Virus Type 1 - Halford, William P. (American Society for Microbiology, 2004)
It is often stated that individuals of a species can differ significantly in their innate resistance to infection with herpes simplex virus type 1 (HSV-1). Three decades ago Lopez reported that C57BL/6 mice could survive a 5,000-fold-higher inoculum of HSV-1 given intraperitoneally than mice of the A or BALB/c strain (Nature 258:152-153, 1975). Susceptible strains of mice died of encephalitis-like symptoms, suggesting that viral spread to the central nervous system was the cause of death. Although Lopez's study documented that C57BL/6 mice were resistant to the development of HSV-1 encephalitis and mortality, the resistance of C57BL/6 mice to other steps of the HSV-1 infection process was not assessed. The results of the present study extend these observations to clarify the difference between resistance to (i) HSV-1 pathogenesis, (ii) HSV-1 replication, (iii) HSV-1 spread, and (iv) the establishment of latent HSV-1 infection. Although C57BL/6 mice are more resistant to HSV-1 pathogenesis than BALB/c mice, the results of the present study establish that HSV-1 enters, replicates, spreads, and establishes latent infections with virtually identical efficiencies in C57BL/6 and BALB/c mice. These observations raise questions about the validity of the inference that differences in natural resistance are relevant in explaining what differentiates humans with recurrent herpetic disease from the vast majority of asymptomatic carriers of HSV-1 and HSV-2.